(untitled) (American Journal of Pedagogical and Educational Research, 2024)
It is known that learning to read information in a foreign language and apply it in the professional field is one of the current issues. This article is devoted to the issue of organizing the step-by-step development of English reading habits and skills of non-philological university students on a technological basis. In addition, extensive information is provided on the technological approach to foreign language teaching.